STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Putri Fauziah; Siti Sofro Siddiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Tourism industry plays an important role in the country’s development. In addition, tourism also has an influence on the revenue for local government. Siak is one of the areas in Riau Province which has variety tourist attractions. One of tourist attractions is Mangrove Ecotourism in the District of Sungai Apit. Mangrove Ecotourism has enormous potential to develop. Therefore, a developmental strategy is needed in order to develop and increase the interest of tourists to visit Mangrove Ecotourism.Theory are used in this research is management strategy of Elitan and Anatan and analysis are used is SWOT analysis. The method used in this research is descriptive qualitative. The data were collected through interviews, observations and documentations. The technique of data analysis which used in this research was qualitative method and descriptive approachment.From the results, it can be seen that the develop Mangrove Ecotourism in the District Sungai Apit done the using technology strategy, innovation strategy and operating strategy. SWOT analysis is then performed to determine what strategies are suitable for the developmet of Ecotourism Mangrove in the District Sungai Apit.Keywords : Ecotourism Mangrove, Strategy, Tourism Development